No increased injury risk on artificial turf in Finnish Premier Division football - Immonen, V.; Kurittu, E.; Kuitunen, I.; Vasankari, T.; Leppänen, M. (Clinical Journal of Sport Medicine, 2025)
Objective: To compare the injury risk between natural grass and artificial turf in the male Finnish premier division (Veikkausliiga) matches during the 2019 league season.